The Concept of Keluarga Sakinah (Tranquil Family) in the Perspective of the Qur'an (A Literature Review) - Baiq Latifah Hasanah (Formad English Foundation NTB Jakarta, 2024)
The concept of keluarga sakinah (tranquil family) in Islam represents an ideal family life characterized by peace, love, and mercy, as depicted in the Qur'an. This study aims to explore the understanding and application of keluarga sakinah in both classical and contemporary Qur'anic exegeses and its relevance to modern family life. Through a literature review, the research examines key Qur'anic verses related to family life, such as Surah Ar-Rum (30:21), Surah At-Tahrim (66:6), and Surah Al-Baqarah (2:233), highlighting the significance of love, affection, mutual responsibility, and religious education within the family. The study also discusses the complementary roles of husband and wife in achieving family harmony, with the husband as the protector and the wife as the nurturer. Findings suggest that the values of keluarga sakinah, such as love, shared responsibility, and justice, remain highly applicable in contemporary society to promote a harmonious family life. The research concludes by emphasizing the importance of implementing these Qur'anic teachings to strengthen family bonds and foster a spiritually and socially balanced household.